Pulmonary embolism in a patient with viral pneumonia: COVID-19 or H1N1 influenza: two case reports - S. K. Kononov; O. V. Solovev; I. S. Metelev; D. E. Nazarov; A. V. Pshenichnikova; D. A. Khomyakov (Российский кардиологический журнал, 2024)
The article presents two case reports of pulmonary embolism in patients with viral pneumonia. In one case, in a coronavirus disease 2019 (COVID-19) survivor, while in the second case — in a patient with influenza. A comparative analysis of thromboembolism characteristics in two patients is consistent with the literature data and confirms the differences in its predictors and the different clinical picture. Pulmonary embolism is becoming an increasingly relevant disease for cardiologists. The importance of understanding the risk factors for pulmonary embolism and clinical picture aspects in patients with viral pneumonia in the current epidemiological situation with both a COVID-19 and seasonal pathogens, including the influenza virus, is emphasized.